The Role of Green Brand Positioning, Knowledge, and Attitude to Improve Green Product Purchase Intention - Audia Dewi Arifani; Rini Kuswati (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to examine how Green Brand Positioning, Green Brand Knowledge, and Attitude Toward Green Brand influence consumer intention to purchase Fore Coffee's environmentally friendly products. Methodology: The research uses an explanatory approach with quantitative methods. A total of 180 participants were selected using a purposive sampling technique. Data were analyzed using SmartPLS 3.0 software with the Partial Least Square (PLS) method. Results: The analysis reveals that Green Brand Positioning, Green Brand Knowledge, and Attitude Toward Green Brand each have a significant and positive impact on Green Product Purchase Intention. Stronger green brand positioning, higher consumer knowledge about environmentally friendly brands, and more positive attitudes toward green brands all contribute to increased purchase intention for eco-friendly products. Applications/Originality/Value: The study highlights the importance of strengthening green brand positioning and enhancing consumer awareness of environmentally friendly products. These insights are valuable for companies in designing effective marketing strategies focused on sustainability and building a positive brand image that encourages eco-friendly purchasing behavior.